(3QSGdI aj bhdg JYGdi hdh Yde Gddg GdBjIs - (3GdMSjfj, GdNGOej, GdfbTHfOj, GdMfaj, CHh SYjO, eMeO Hf eUWai Hf YKeGf, J (B1176 (3g`s ((3eOjfI GdNGOfs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO defRd GdcJGH hHYO agPg cdeGJ eJYdbI Ydi bhdg JYGdi aj ShQI GdCfaGd hdh Yde Gddg ajge NjQG dCSeYge hdh CSeYge dJhdhGs
(3BNQgG (B:s
(3UGOQ eef aj GdbUhQ aGFb HEdMGM HYV MQGU GdWdGH ef GdCMHGH efVeG Edi EVeGQ eG aj GdaDGO dSHb HMKg eY HYV Phj GdCdHGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 68s
(3eYLe GdeDdajf (B3 / 693s
(3SQcjS (B808s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJaSjQ hYdhe GdbQBfs